Semiotic analysis of sexual harassment representation in the film “Penyalin Cahaya” - Kirana Pinkan Permata Rudy; Christina Nur Wijayanti (Institute of Computer Science (IOCS), 2023)
he purpose of this study is to describe what representations of sexual harassment are contained in the film